2008
DOI: 10.1161/hypertensionaha.108.111369
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Remodeling and Duration of Hypertension Predict Outcome of Adrenalectomy in Primary Aldosteronism Patients

Abstract: Abstract-Remodeling of the resistance arteries is a hallmark of arterial hypertension and predicts cardiovascular events, but it was unknown whether it could also predict the blood pressure response to adrenalectomy of patients with an aldosterone-producing adenoma. Therefore, we investigated the outcome of adrenalectomy as a function of vascular remodeling in the context of the preoperative features of aldosterone-producing adenoma patients. At 2 referral centers for hypertension, we prospectively measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(132 citation statements)
references
References 35 publications
10
113
3
6
Order By: Relevance
“…In agreement with the previous studies (18,19,24), in our group of patients, duration of hypertension can be considered as a prognostic factor; shorter hypertension duration gives a higher recovery percentage. In particular, the ROC curve analysis showed that the best predictor of hypertension recovery after surgery is the duration of hypertension equal to or shorter than 6 years, in accordance with a recent study by Zarnegar et al (18).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with the previous studies (18,19,24), in our group of patients, duration of hypertension can be considered as a prognostic factor; shorter hypertension duration gives a higher recovery percentage. In particular, the ROC curve analysis showed that the best predictor of hypertension recovery after surgery is the duration of hypertension equal to or shorter than 6 years, in accordance with a recent study by Zarnegar et al (18).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, 63% of our APA patients were cured of hypertension (blood pressure below 140/90 mmHg, without the aid of antihypertensive medications), while blood pressure levels improved in the remaining patients. Such results are in line with the literature data reporting a rate of blood pressure normalization ranging between 30 and 70% (19,24). This broad range comes from studies performed with different data collection methods and with different definition of cure/improvement of hypertension (18,19,21,28).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…L'existence d'une corrélation stricte entre le génotype et le phénotype a été récem-ment nuancée par la description d'un patient porteur d'une mutation hétérozygote germinale p.Gly151Arg, qui avait développé une polyurie à l'âge de 18 mois et une hypertension avec hypokaliémie à 4 ans. Par la suite, son hyper aldostéronisme a été traité avec succès durant sept ans avec de la spironolactone 6 sans que soit observé un élargissement de la surrénale [31]. Dans tous les cas, la recherche de mutations dans le gène KCNJ5 doit être considérée même dans les formes familiales modérées d'HAP.…”
Section: Anomalies De Kcnj5 Dans L'hyperaldostéronisme Primaire Familialunclassified
“…À long terme, le traitement de l'hyperaldostéronisme primaire permet une réversibilité de l'hypertrophie ventriculaire gauche [5]. Le remodelage vasculaire dû à l'excès d'aldostérone ainsi que la durée de l'hypertension constituent des indicateurs de la réponse de la pression artérielle à la surrénalectomie, soulignant ainsi l'importance d'un diagnostic précoce de la maladie [6]. La production d'aldostérone par la zone glomérulée du cortex surréna-lien est finement régulée afin d'assurer le maintien de l'homéostasie hydrosodée au niveau rénal (Figure 1).…”
unclassified